Ostial atresia of the coronary sinus in patients with supraventricular arrhythmias. Issue 3 (16th May 2019) - Hiroshima, Ken‐ichi; Goya, Masahiko; Nagashima, Michio; Fukunaga, Masato; Ohe, Masatsugu; An, Yoshimori; Makihara, Yu; Hayashi, Kentaro; Ando, Kenji
Abstract: Of 3577 patients with supraventricular arrhythmias, 3 demonstrated an atresia of the coronary sinus (CS) ostium. Two patients had the accessory pathways. One had atrial fibrillation. No unroofed CS or apparent persistent left superior vena cava was observed. Venous drainage through a small cardiac vein located on the lateral portion of the tricuspid annulus was observed in all patients. Those cases demonstrated that the incidence of ostial atresia of the CS was 0.084%. Accessory pathways were often accompanied by this anomaly. An abnormal venous orifice located on the lateral tricuspid annulus often functioned as the drainage of the CS flow.